Minimum Dataset Required to Collect from Agronomic Field Experimentation - Devkota Wasti, Mina Kumari; Attaher, Samar; Devkota, Krishna (International Center for Agricultural Research in the Dry Areas, 2022)
Implementing strategic field experimentation not only provide opportunities to solve the research questions but also provide a useful way to address a number of important issues in crop, soil, water, environmental and resource economics using different analytical tools. As implementing field experimentation is resource intensive (cost, time and energy), it is important to plan for collecting/generating standard data set (both quality and minimum number).